Dynamic random lasing in silica aerogel doped with rhodamine 6G - Wetter, Niklaus Ursus (2018)
Silica aerogel is a lightweight material, well known for its good mechanical and thermal characteristics, but its optical properties have received less attention, because it is weakly scattering. Here we present for the first time the lasing properties and their complex dynamics of silica aerogel doped with R6G. It is shown that the Q factors of the lasing modes determine the operation of the laser, being either resonant or ASE-lasing. For resonant lasing, the number of resonators is easily varied and the number of modes in a single resonator and their emission frequency can be dynamically adjusted, making this a truly versatile photonics material.